Effect Of Chlorides And Sulphates On Esp-Ggbs Based Alkali Activated Concrete At Different Molarities - et. al., Polusani Sharada, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Construction industry is playing a vital role in the deterioration of the environment by depleting natural resources, utilizing huge quantities of energy from fossil fuels. Conventional concrete production which uses cement as a constituent is one of the major contributors to emissions of greenhouse gases. Usage of Alkali-activated concrete is gaining importance in the recent past since it imparts less carbon footprint on the environment. Other eco-friendly alternative solutions can be adopted to reduce the depletion of resources. In the present study, Egg Shell Powder (ESP) and GGBS are used as an alternate source of the binder. Eggshell powder and GGBS can be activated through the alkaline solution, which polymerizes these materials into molecular chains and networks to create a hardened binder. In this paper apart from Eggshell powder and GGBS, Robo sand which is an excellent substitute for depleting natural sand was used which makes the alkali-activated concrete furthermore advantageous. In this paper, the results of the detailed study done on alkali-activated concrete immersed in HCL and H2SO4 are presented. Workability test is done on fresh concrete and durability, compressive strength test is done on hardened concrete. Compressive strength of alkali-activated concrete has been reported with varying percentages of GGBS and ESP (G90E10, G80E20, G70E30, G60E40) at 8, 10 and 12 Molarities. NaOH and Na2Sio3 are used as Alkali Activators. Also, results of percentage loss in Compressive strength and Weight of cubes immersed in HCL and H2So4 are presented.